Malaysian English: Attitudes and awareness in the Malaysian context - Nair, Umavathy Govendan (Journal of Modern Languages, 2017)
To compare the attitudes of Malaysians towards Malaysian English, a study was conducted among 80 teachers and 80 non-teachers. The subjects were chosen from various parts of the country, i.e. urban and rural, so as to obtain valid findings.